(3GdfXGe GdbGfhfj ddfbd GdOhdj eJYOO GdhSGFW (B/ s - (3aGQhb eMeO edTs; (3eMSf Tajb (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B-(3LGeYI GdbGgQI,s, 1994)
(3JfbSe GdQSGdI Edi HGH JegjOj GdPj jJfGhd GdedGeM GdQFjSjI ddfbd GdOhdj eJYOO GdhSGFW, Ke GdbSe GdChd CMcGe Gdfbd GdOhdj eJYOO GdhSGFW, hGdbSe GdKGfj Yf GdLhGfH GdJWHjbjI ddfTGW GdbGfhfj deJYgO Gdfbd eJYOO GdhSGFW(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1994.s
(3HHdjhLQGajG(B: (3UaMGJ(B531-551.s
Keywords: (3Gdfbd GdOhdjs; (3YbO Gdfbds; (3Gdfbd GdOhdj eJYOO GdhSGFWs; (3hKjbI Gdfbd GdOhdj eJYOO GdhSGFWs; (3GJaGbjI GdCee GdeJMOI HTCf Gdfbd GdHMQj ddHVGFY s; (3eSFhdjI GdfGbds; (3SfO GdTMfs; (3GJaGbjI Gdfbd eJYOO GdhSGFWs; (3bhGYO gGeHhQL HTCf Gdfbd GdHMQjs; (3GdJMcje aj efGRYGJ Gdfbd GdHMQjs; (3Gdfbd GdOhdjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 1994